Sistem Informasi Pendaftaran Santri Baru Berbasis WEB dengan Pemanfaatan UML Pada PONPES Daarun Nizham - Nurul Ichsan, Nurul Ichsan; Ichsan, Nurul; Alfarizi, Salman; Gunawan, Deni; Mulyawan, Alif Rizqi; Basri, Hasan (PROFITABILITAS, 2021)
Abstracts - The shift in the way of life in modern society which is increasingly complex, encourages people to find ways to adapt and survive to face technological advances globally in all aspects of life needs. In the use of technology and information, one of  them is PONPES Daarun Nizham trying to present a religious touch that is grounded in the progress of the times by trying to develop a typical Islamic organization with the application of modern information systems and technology. Judging from several aspects of the weakness of the new student registration recruitment process which is still carried out manually, the design of the new student registration program is carried out in an integrated manner with the internet network. is considered to be one of the powerful solutions to answer the needs of agencies in the manual registration process. The method used by the author is waterfall method. Based on the description of the problem above, it is necessary to create a system in the form of research regarding the Design of a-based New Student Registration Program web at PONPES Daarun Nizham. On This website will display information about the data registries, data completeness students, confirmation of payment, academic potential test, print documents and reports (PSB). With this website, it can make it easier for prospective new students in the student registration process so that the problem of distance between pesantren and new students can be resolved by online registration and is the best solution for Islamic boarding schools in solving problems that occur and the recruitment process for new students can be carried out effectively and efficiently without compromising the uniqueness and authenticity of the santri recruitment ritualistic that has been carried out at PONPES Daarun Nizham.